Automated activity monitoring of estrus and time of ovulation - Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 2013)
Detection of estrus can be facilitated by use of automated activity monitors that measure physical activity. Increased physical activity is largely correlated with estrus. Our objective was to determine when ovulation occurs relative to increased physical activity so we could recommend optimal timing of insemination to maximize conception rates in lactating dairy cows. Cows (n = 65) were fitted with pressure-sensitive rump-mounted transmitters (HeatWatch; HW) that are activated by a mounting herdmate to indicate standing estrus. The same cows also were fitted with neck-mounted activity monitors (Select Detect; SD). Additional cows (n = 68) were fitted with only the activity monitor. Beginning approximately 14.5 hours after the individual activity monitor on a cow reached a set threshold, transrectal ultrasonography was used to identify the ovarian preovulatory follicle. Repeated ovarian scans were performed every 3 hours until ovulation occurred or 36 hours after threshold was reached. Although average intervals to ovulation actually differed (P<0.05) by only 1.5 h (27.2 ± 0.6 h for HW vs. 25.7 ± 0.4 h for SD), deviations between onsets differed by 2.0 ± 0.4 h (increased activity preceded time of standing to be mounted). Increased physical activity tended to increase before the first standing event and endured longer than the duration of estrus measured by HW. We concluded that the activity monitor was a reliable tool to detect estrus, and ovulation occurred at similar intervals from increased activity as from the first standing event associated with estrus.; Dairy Day, 2013, Kansas State University, Manhattan, KS, 2013; Dairy Research, 2013 is known as Dairy Day, 2013
Keywords: Dairy Day; 2013; Kansas Agricultural Experiment Station contribution; no. 14-179-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 1093; Estrus; Ovulation; Physical activity